FAKTOR YANG MEMPENGARUHI KEINGINAN PINDAH KERJA GURU SEKOLAH DASAR SWASTA DI KOTA BATAM - Heri Ristianto; Lily Sudhartio (JWM (JURNAL WAWASAN MANAJEMEN), 2022)
ABSTRACTThe purpose of this study is to try to identify whether the variables of job satisfaction, performance and work environment affect the turnover intention of private elementary school teachers in Batam City. This research was conducted from January to March 2020. The selection of the schools sampled in this study used a non-probability sampling method. The population in this study involved 3213 private elementary school teachers scattered in Batam City, while teachers who were directly involved as respondents were 350 teachers from 16 private elementary schools spread across ten sub-districts in Batam city. Distribution of questionnaires to respondents is done via Google form. The data were obtained by distributing questionnaires and then analyzed using multiple linear regression. The results of this study illustrate that there is a negative and significant effect of job satisfaction on turnover intention variables. The work environment also has a significant negative effect on turnover intention. Meanwhile, performance has no influence on the dependent variable.